The Examination of Olfactory Function and Mucocilliary Transport in Gas Station Officers in Makassar, Indonesia (Nusantara Medical Science Journal, 2022)
Introduction: Chronic exposure to fuel oil can cause chemical burns to the olfactory epithelium, which can cause anosmia. This study aimed to compare mucociliary transport time and olfactory function between operator and non-operator officers at gas stations. Methods: This cross-sectional study was conducted from September to November 2020 and involved 40 subjects divided into two equal groups each consisting of 20 gas station operators and non-operators, respectively. The examination of mucociliary transport time was carried out by saccharin test, while the olfactory function was examined by assessing e olfactory threshold, discrimination, and identification (TDI) score using the Sniffin sticks test. Results: There was a significant difference in the mean mucociliary transport time and olfactory function between gas station operators and non-operators (P